Fractional Flow Reserve-Guided PCI as Compared with Coronary Bypass Surgery - Fearon, William F; Zimmermann, Frederik M; De Bruyne, Bernard; Piroth, Zsolt; van Straten, Albert H M; Szekely, Laszlo; Davidavičius, Giedrius; Kalinauskas, Gintaras; Mansour, Samer; Kharbanda, Rajesh; Östlund-Papadogeorgos, Nikolaos; Aminian, Adel; et al. (The New England journal of medicine, 2022)
BACKGROUND: Patients with three-vessel coronary artery disease have been found to have better outcomes with coronary-artery bypass grafting (CABG) than with percutaneous coronary intervention (PCI), but studies in which PCI is guided by measurement of fractional flow reserve (FFR) have been lacking. METHODS: In this multicenter, international, noninferiority trial, patients with three-vessel coronary artery disease were randomly assigned to undergo CABG or FFR-guided PCI with current-generation zotarolimus-eluting stents. The primary end point was the occurrence within 1 year of a major adverse cardiac or cerebrovascular event, defined as death from any cause, myocardial infarction, stroke, or repeat revascularization. Noninferiority of FFR-guided PCI to CABG was prespecified as an upper boundary of less than 1.65 for the 95% confidence interval of the hazard ratio. Secondary end points included a composite of death, myocardial infarction, or stroke; safety was also assessed. RESULTS: A total of 1500 patients underwent randomization at 48 centers. Patients assigned to undergo PCI received a mean (±SD) of 3.7±1.9 stents, and those assigned to undergo CABG received 3.4±1.0 distal anastomoses. The 1-year incidence of the composite primary end point was 10.6% among patients randomly assigned to undergo FFR-guided PCI and 6.9% among those assigned to undergo CABG (hazard ratio, 1.5; 95% confidence interval [CI], 1.1 to 2.2), findings that were not consistent with noninferiority of FFR-guided PCI (P = 0.35 for noninferiority). The incidence of death, myocardial infarction, or stroke was 7.3% in the FFR-guided PCI group and 5.2% in the CABG group (hazard ratio, 1.4; 95% CI, 0.9 to 2.1). The incidences of major bleeding, arrhythmia, and acute kidney injury were higher in the CABG group than in the FFR-guided PCI group. CONCLUSIONS: In patients with three-vessel coronary artery disease, FFR-guided PCI was not found to be noninferior to CABG with respect to the incidence of a composite of death, myocardial infarction, stroke, or repeat revascularization at 1 year. (Funded by Medtronic and Abbott Vascular; FAME 3 ClinicalTrials.gov number, NCT02100722.).
Keywords: Cardiovascular Diseases; senioři; koronární stenóza; Male; Female; Kaplanův-Meierův odhad; frakční průtoková rezerva myokardu; Percutaneous Coronary Intervention; Aged; délka operace; Middle Aged; Kaplan-Meier Estimate; Coronary Artery Bypass; Coronary Stenosis; Fractional Flow Reserve, Myocardial; stenty; Operative Time; délka pobytu; Stents; Length of Stay; mužské pohlaví; koronární angioplastika; koronární bypass; ženské pohlaví; Reoperation; reoperace; lidé středního věku; kardiovaskulární nemoci; lidé; Humans